Status of Arsenic Contamination in Groundwater of Makar VDC of Nawalparasi District, Nepal - Bhusal, Shreejana; Paudyal, Kabiraj (International Journal of Environment, 2014)
Arsenic is one of the 92 natural elements found in Earth crust which is referred as" King of Poison". Arsenic contamination in groundwater has been recognized as a great threat to water supply and public health in many countries in the world (WHO 1993). Therefore this research work was done with the objectives to assess the concentration of arsenic in groundwater at Makar VDC of Nawalparasi district by both field kit test and Atomic Absorption Spectrometry (AAS) test methods and assess the possible natural sources of arsenic mobilization in groundwater and further identify the safe and contaminated aquifers and their distribution below the ground. Based on the field and laboratory analysis it is concluded that the aquifer lying in between 30-70 feet is contaminated with arsenic in toxic level (>50 ppb) while the horizons of aquifers shallower or deeper than this depth are found safe. Present study also showed about 38%, 23%, 19% and 20 % of aquifers as safe tolerable, toxic and very toxic respectively. Study on the mineralogical composition of the soil and sediment showed that it is rich in arsenic bearing minerals like pyrite, biotitic, iron-coatings and opaque minerals. These minerals are considered potential sources of release of arsenic in groundwater under reducing environment. No adverse health effects are seen on people although the concentration is found in toxic level. This might be either due to hesitation of people to expose their infected organ in front of the research students or the researcher's inability to identify the symptoms, as it has no normal symptoms and need the experts from the medical field. Present study is able to pinpoint the depth of contaminated aquifer, which is useful for the safe drinking water development strategy. DOI: http://dx.doi.org/10.3126/ije.v3i3.11087 International Journal of Environment Vol.3(3) 2014: 275-285